Increasing the low-risk threshold for patients with upper gastrointestinal bleeding during the COVID-19 pandemic: a prospective, multicentre feasibility study. Issue 4 (25th August 2021) - Dunne, Philip; Livie, Victoria; McGowan, Aaron; Siu, Wilson; Chaudhary, Sardar; Groome, Maximillian; Phull, Perminder; Fraser, Andrew; Morris, Allan John; Penman, Ian D; Stanley, Adrian J
Abstract : Objective: During the COVID-19 pandemic, we extended the low-risk threshold for patients not requiring inpatient endoscopy for upper gastrointestinal bleeding (UGIB) from Glasgow Blatchford Score (GBS) 0–1 to GBS 0–3. We studied the safety and efficacy of this change. Methods: Between 1 April 2020 and 30 June 2020 we prospectively collected data on consecutive unselected patients with UGIB at five large Scottish hospitals. Primary outcomes were length of stay, 30-day mortality and rebleeding. We compared the results with prospective prepandemic descriptive data. Results: 397 patients were included, and 284 index endoscopies were performed. 26.4% of patients had endoscopic intervention at index endoscopy. 30-day all-cause mortality was 13.1% (53/397), and 33.3% (23/69) for pre-existing inpatients. Bleeding-related mortality was 5% (20/397). 30-day rebleeding rate was 6.3% (25/397). 84 patients had GBS 0–3, of whom 19 underwent inpatient endoscopy, 0 had rebleeding and 2 died. Compared with prepandemic data in three centres, there was a fall in mean number of UGIB presentations per week (19 vs 27.8; p=0.004), higher mean GBS (8.3 vs 6.5; p<0.001) with fewer GBS 0–3 presentations (21.5% vs 33.3%; p=0.003) and higher all-cause mortality (12.2% vs 6.8%; p=0.02). Predictors of mortality were cirrhosis, pre-existing inpatient status, age >70 and confirmed COVID-19. 14 patients were COVID-19 positive, 5 died but none from UGIB. Conclusion: During the pandemic when services were under severe pressure, extending the low-risk threshold for UGIB inpatient endoscopy to GBS 0–3 appears safe. The higher mortality of patients with UGIB during the pandemic is likely due to presentation of a fewer low-risk patients.